Light charged-particle production in 96 MeV neutron-induced reactions on carbon and oxygen - Tippawan U. (2014)
In recent years, an increasing number of applications involving fast neutrons have been developed or are under consideration, e.g. radiation treatment of cancer, neutron dosimetry at commercial aircraft altitudes, soft-error effects in computer memories, accelerator-driven transmutation of nuclear waste and energy production and determination of the response of neutron detectors. Data on light-ion production in light nuclei such as carbon, nitrogen and oxygen are particularly important in calculations of dose distributions in human tissue for radiation therapy at neutron beams, and for dosimetry of high-energy neutrons produced by high-energy cosmic radiation interacting with nuclei (nitrogen and oxygen) in the atmosphere. When studying neutron dose effects, it is especially important to consider carbon and oxygen, since they are, by weight, the most abundant elements in human tissue. Preliminary experimental double-differential cross sections of inclusive light-ion (p, d, t, 3He and α) production in carbon induced by 96-MeV neutrons have been presented. Energy spectra were measured at eight laboratory angles: 20, 40, 60, 80, 100, 120, 140 and 160°. Measurements were performed at The Svedberg Laboratory (TSL), Uppsala, using the dedicated MEDLEY experimental setup. The authors have earlier reported experimental double-differential cross sections of inclusive light-ion production in oxygen. In this paper, the deduced kerma coefficients for oxygen has been presented and compared with reaction model calculations. © The Author 2007. Published by Oxford University Press. All rights reserved.